Changing Sediment Dynamics of a Mature Backbarrier Salt Marsh in Response to Sea-Level Rise and Storm Events - Schuerch, Mark; Dolch, Tobias; Bisgwa, Julian; Vafeidis, Athanasios T. (Frontiers in Marine Science, 2018)
Our study analyses the long-term development of a tidal backbarrier salt marsh in the northern German Wadden Sea. The focus lies on the development of the high-lying, inner, mature part of the salt marsh, which shows a striking history of changing sediment dynamics. The analysis of high-resolution old aerial photographs and sampled sediment cores suggests that the mature part of the marsh was shielded by a sand barrier from the open sea for decades. The supply with fine-grained sediments occurred from the marsh inlet through the tidal channels to the inner salt marsh. Radiometric dating (210Pb and 137Cs) reveals that the sedimentation pattern changed fundamentally around the early-mid 1980s when the sedimentation rates increased sharply. By analyzing the photographic evidence, we found that the sand barrier was breached during storm events in the early 1980s. As a result, coarse-grained sediments were brought directly through this overwash from the sea to the mature part of the salt marsh and increased the sedimentation rates. We show that the overwash and the channels created by these storm events built a direct connection to the sea and reduced the distance to the sediment source which promoted salt marsh growth and a supply with coarse-grained sediments. Consequently, the original sediment input from the tidal channels is found to play a minor role in the years following the breach event. The presented study showcases the morphological development of a mature marsh, which contradicts the commonly accepted paradigm of decreasing sedimentation rates with increasing age of the marsh. We argue that similar trends are likely to be observed in other backbarrier marshes, developing in the shelter of unstabilized sand barriers. It further highlights the question of how resilient these salt marshes are towards sea level rise and how extreme storm events interfere in determining the resilience of a mature salt marsh.